1990
DOI: 10.1111/j.1365-2788.1990.tb01521.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of functional analyses to test causes of self‐injurious behaviour: rationale, current status and future directions

Abstract: ABSTRACT. Self-injurious behaviour (SIB) is a relatively common phenomenon among severely retarded persons and involves various repetitious behaviours resulting in tissue damage. Perhaps because of the damage it does, the behaviour has generated a considerable amount of applied research and discussion, and much of this research has involved attempts to reduce SIB through the manipulation of antecedents or consequences. The purpose of this paper was to determine the extent to which those conducting this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Higher than expected efficacy ratings were found when functional analyses were conducted. This supports the finding of Scotti et al (1991), and reinforces the position of Repp et al (1990) that a functional analysis is an important component leading to intervention success. Unfortunately, the present data indicate that functional analyses were only conducted on 29% of the subjects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Higher than expected efficacy ratings were found when functional analyses were conducted. This supports the finding of Scotti et al (1991), and reinforces the position of Repp et al (1990) that a functional analysis is an important component leading to intervention success. Unfortunately, the present data indicate that functional analyses were only conducted on 29% of the subjects.…”
Section: Discussionsupporting
confidence: 90%
“…The issue most recently has been the appropriateness of certain types of interventions (Donnellan et al 1988;Lovaas & Favell 1987: Luiselli 1989Matson & Taras 1989;Sternberg & Taylor 1994;Tamowski et al 1989). Of related import is the body of work investigating the potential function that SIB might serve for the individual, and the role that functional analysis might play in the selection and effectiveness of an appropriate intervention (Carr 1988;Durand & Crimmins 1988;Repp et al 1990). Lundervold & Bourland (1988) reviewed a number of issues pertaining to the use of various interventions designed to decrease or eliminate aggression, self-injury or property destruction exhibited by individuals with developmental disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…By and large, responders reported that lack of time for conducting functional analyses served as their biggest barrier. The time required to conduct a functional analysis (i.e., analytic efficiency) has been commonly recognized as a limitation of the functional analysis (e.g., Cooper, Heron, & Heward, ; Repp, Singh, Olinger, & Olson, ), with some reporting functional analysis to require a mean of 6.5 hr and a range of up to 16.5 hr to conduct (Iwata et al, ).…”
mentioning
confidence: 99%
“…Durand & Carr, 1987;Repp el al., 1988;Runco et al. 1986;Steege et al, 1989), the majority of intervention studies are devoid of a structural or functional analysis of stereotypy (see Repp et al, 1990). As a result little has been learned about its nature or about the variables that may be responsible for its occurrence.…”
Section: Introductionmentioning
confidence: 99%